Embryonic origin of primary colon cancer predicts survival in patients undergoing ablation for colorectal liver metastases. Issue 6 (June 2017) - Yamashita, S.; Odisio, B.C.; Huang, S.Y.; Kopetz, S.E.; Ahrar, K.; Chun, Y.S.; Conrad, C.; Aloia, T.A.; Gupta, S.; Harmoush, S.; Hicks, M.E.; Vauthey, J.-N.
Abstract: Background: In patients with primary colorectal cancer (CRC) or unresectable metastatic CRC, midgut embryonic origin is associated with worse prognosis. The impact of embryonic origin on survival after ablation of colorectal liver metastases (CLM) is unclear. Methods: We identified 74 patients with CLM who underwent percutaneous ablation during 2004–2015. Survival and recurrence after ablation of CLM from midgut origin (n = 18) and hindgut origin (n = 56) were analyzed. Prognostic value of embryonic origin was evaluated. Results: Recurrence-free survival (RFS) and overall survival (OS) after percutaneous ablation were worse in patients from midgut origin (3-year RFS: 5.6% vs. 24%, P = 0.004; 3-year OS: 25% vs. 70%, P 0.001). In multivariable analysis, factors associated with worse OS were midgut origin (hazard ratio [HR] 4.87, 95% CI 2.14–10.9, P 0.001), multiple CLM (HR 2.35, 95% CI 1.02–5.39, P = 0.044), and RAS mutation (HR 2.78, 95% CI 1.25–6.36, P = 0.013). At a median follow-up of 25 months, 56 patients (76%) had developed recurrence, 16 (89%) with midgut origin and 40 (71%) with hindgut origin ( P = 0.133). Recurrent disease was treated with local therapy in 20 patients (36%), 2 (13%) with midgut origin and 18 (45%) with hindgut origin ( P = 0.022). Conclusion: Compared to CLM from hindgut origin tumors, CLM from midgut origin tumors were associated with worse survival after ablation, which was partly attributable to the fact that patients with hindgut origin were more frequently candidates for local therapy at recurrence.